Stress Distribution in Single Dental Implant System: Three-Dimensional Finite Element Analysis Based on an In Vitro Experimental Model - Edwards Rezende, Carlos Eduardo; Chase-Diaz, Melody; Costa, Max Doria; Albarracin, Max Laurent; Paschoeto, Gabriela [UNESP]; Capello Sousa, Edson Antonio [UNESP]; Rubo, Jose Henrique; Sanches Borges, Ana Flavia (Lippincott Williams & Wilkins, 2015)
This study aimed to analyze the stress distribution in single implant system and to evaluate the compatibility of an in vitro model with finite element (FE) model. The in vitro model consisted of Branemark implant; multiunit set abutment of 5mm height; metal-ceramic screw-retained crown, and polyurethane simulating the bone. Deformations were recorded in the peri-implant region in the mesial and distal aspects, after an axial 300N load application at the center of the occlusal aspect of the crown, using strain gauges. This in vitro model was scanned with micro CT to design a three-dimensional FE model and the strains in the peri-implant bone region were registered to check the compatibility between both models. The FE model was used to evaluate stress distribution in different parts of the system. The values obtained from the in vitro model (20-587 epsilon) and the finite element analysis (81-588 epsilon) showed agreement among them. The highest stresses because of axial and oblique load, respectively were 5.83 and 40MPa for the cortical bone, 55 and 1200MPa for the implant, and 80 and 470MPa for the abutment screw. The FE method proved to be effective for evaluating the deformation around single implant. Oblique loads lead to higher stress concentrations.
Keywords: Dental implants; dental prostheses; finite element analysis